Does Treatment Duration of Problem-Based Learning Moderate Heterogeneity of Students’ Mathematical Critical Thinking Skills? A Meta-Analysis - Suparman Suparman; Dadang Juandi; Bambang Avip Priatna Martadiputra (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2021)
This study aims to investigate and examine PBL treatment duration predicted as a potential factor moderating heterogeneity of students' MCTS. A meta-analysis by selecting the random effect model was employed to conduct this study. Data analysis used the Q Cochrane test and Z test supported by Comprehensive Meta-Analysis (CMA) software. A literature search found 220 documents, and the final literature selection established 23 documents in journal articles and 4 documents in proceeding articles indexed by Scopus, Google Scholar, or Web of Science and published in the period of 2013 – 2021. The results revealed that the p-value of the Q statistic related to the factor of PBL treatment duration was less than 0,05 (p = 0,535). It indicates that PBL treatment duration is not a significant factor moderating heterogeneity of students' MCTS. It interprets that the gap of students' MCTS level through PBL is not caused by the treatment duration factor. Furthermore, PBL treatment in the period of 3 – 6 months was more effective to enhance students' MCTS than PBL treatment duration was less than 3 months or more than 6 months. For a further similar meta-analysis study, other researchers should investigate and examine other potential factors such as PBL class capacity and students’ demography that are able to moderate heterogeneity of students’ MCTS